1996
DOI: 10.2169/internalmedicine.35.953
|View full text |Cite
|
Sign up to set email alerts
|

Carcinoid Tumor of the Gall Bladder.

Abstract: A classical carcinoid tumor, measuring ll x 17 mm, was found in a 41-year-old womanin the neck of the gall bladder. The lesion infiltrated the muscular layer of the gall bladder wall. Histologically, the tumor was positive for only Grimelius and chromogranin A stains. In a literature search, approximately half of the tumors reported as gall bladder carcinoid tumor appear to be actually endocrine cell carcinomas, which are completely different from classical carcinoid tumors with respect to size, metastasis and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 15 publications
1
24
0
1
Order By: Relevance
“…Nevertheless the mitotic index and the differentiation have not always been reported together in the description of GB-NENs cases. The majority of GB-NENs are diagnosed during histological examination at autopsy or after surgery for cholelithiasis or other suspected biliary pathology [5][6][7]. Considering the pathogenesis of GB-NENs, cholelithiasis and chronic gallbladder wall inflammation are associated with GB-NENs in virtually all published cycles of chemotherapy (Figs.…”
Section: Case Presentationmentioning
confidence: 99%
“…Nevertheless the mitotic index and the differentiation have not always been reported together in the description of GB-NENs cases. The majority of GB-NENs are diagnosed during histological examination at autopsy or after surgery for cholelithiasis or other suspected biliary pathology [5][6][7]. Considering the pathogenesis of GB-NENs, cholelithiasis and chronic gallbladder wall inflammation are associated with GB-NENs in virtually all published cycles of chemotherapy (Figs.…”
Section: Case Presentationmentioning
confidence: 99%
“…Endocrine cells have been identified in the mucosa of the gallbladder neck and may have been the origin of this neoplasm. 4 Biliary carcinoid tumors are rare neoplasms of the extrahepatic biliary tree including the gallbladder with approximately 30 cases reported in humans and none in domestic animals. 1 Although potentially malignant in humans, carcinoid tumors are usually slow growing with a 5-year survival rate of 94% if localized, 64% if regional metastasis is present, and 18% if distant metastasis has occurred at the time of diagnosis.…”
mentioning
confidence: 99%
“…Carcinoid tumor of the gallbladder was first reported by Joel in 1929 [3] and first reported in Japan by Funabashi et al [4] in 1978. Carcinoid tumors, previously a generic term for endocrine tumors, are classified into two categories, classical carcinoid tumors and endocrine cell carcinomas [4][5][6]. There remains confusion about the definition of carcinoid tumors, which has led to a poor understanding of these lesions.…”
Section: Discussionmentioning
confidence: 99%
“…There remains confusion about the definition of carcinoid tumors, which has led to a poor understanding of these lesions. Some investigators have described neuroendocrine cell carcinomas of the gallbladder as carcinoid tumors even though they show a distinctively different histological form and natural history [5,6]. Modlin et al [7] pointed out that half of the previously reported cases of carcinoid tumor of the gallbladder should actually be classified as neuroendocrine carcinomas.…”
Section: Discussionmentioning
confidence: 99%